Cow's milk and rice fermented with Lactobacillus paracasei CBA L74 prevent infectious diseases in children: A randomized controlled trial. Issue 1 (February 2017) - Nocerino, Rita; Paparo, Lorella; Terrin, Gianluca; Pezzella, Vincenza; Amoroso, Antonio; Cosenza, Linda; Cecere, Gaetano; De Marco, Giulio; Micillo, Maria; Albano, Fabio; Nugnes, Rosa; Ferri, Pasqualina; et al.
Summary: Background & aim: Fermented foods have been proposed for the prevention of infectious diseases. We evaluated the efficacy of fermented foods in reducing common infectious diseases (CIDs) in children attending daycare. Methods: Prospective randomized, double-blind, placebo-controlled trial (registered under Clinical Trials.gov identifierNCT01909128 ) on healthy children (aged 12–48 months) consuming daily cow's milk (group A) or rice (group B) fermented with Lactobacillus paracasei CBA L74, or placebo (group C) for three months during the winter season. The main study outcome was the proportion of children who experienced at least one CID. All CIDs were diagnosed by family pediatricians. Fecal concentrations of innate (α- and β-defensins and cathelicidin LL-37) and acquired immunity biomarkers (secretory IgA) were also evaluated. Results: 377 children (193 males, 51%) with a mean (SD) age of 32 (10) months completed the study: 137 in group A, 118 in group B and 122 in group C. Intention-to-treat analysis showed that the proportion of children who experienced at least one CID was lower in group A (51.8%) and B (65.9%) compared to group C (80.3%). Per-protocol analysis showed that the proportion of children presenting upper respiratory tract infections was lower in group A (48.2%) and group B (58.5%) compared with group C (70.5%). The proportion of children presenting acute gastroenteritis was also lower in group A (13.1%) and group B (19.5%) compared with group C (31.1%). A net increase of all fecal biomarkers of innate and acquired immunity was observed for groups A and B compared to group C. Moreover, there was a negative association between fecal biomarkers and the occurrence of CID. Conclusion: Dietary supplementation with cow's milk or rice fermented with L. paracasei CBA L74 prevents CIDs in children attending daycare possibly by means of a stimulation of innate and acquired immunity.